STUDI EKSPLORATIF PERSEPSI GURU TERHADAP KEBIJAKAN BELAJAR DARI RUMAH PADA MASA PANDEMI COVID-19 - Marzoan Marzoan (Lembaga Penelitian dan Pendidikan Mandala, 2020)
This study aims to obtain teacher perceptions about the impact of the implementation of the Learning from Home policy according to a circular from the Minister of Education and Culture dated March 24, 2020, which regulates the implementation of education during the coronavirus spread. The research method uses exploratory case studies, the research approach uses qualitative case study methods which are used to obtain information about the effectiveness of the learning process from home during the Covid-19 pandemic. This research was conducted in June 2020. Respondents of this study were 20 elementary school teachers spread across five districts in North Lombok Regency, West Nusa Tenggara. Respondents were drawn from each elementary school teacher spread over five districts. The data of this study were sourced from the results of questionnaire and interview answers developed based on a review of relevant literature. All respondents filled out a research questionnaire online through the Google forms application, then the questionnaire was confirmed via telephone interview. The results of this study conclude that learning policies from home during the Covid-19 pandemic period according to teacher perceptions have not been implemented well and according to teacher observations, only 25% of students actually carry out learning from home. As many as 60% of teachers feel that their burden becomes heavier when compared to the learning process that has been carried out in classi ﬁ cation or face-to-face and 65% of teachers state that they need additional skills to be able to carry out the learning process from home.